2017
DOI: 10.1515/jvetres-2017-0024
|View full text |Cite
|
Sign up to set email alerts
|

Dogs’ gastrointestinal parasites and their association with public health in Iran

Abstract: IntroductionDogs harbour zoonotic parasites that cause serious infections in humans, such as visceral larva migrans, ocular larva migrans, cystic echinococcosis, and alveolar echinococcosis. Studies on dogs’ gastrointestinal parasites in different geographical locations are required to increase knowledge of the risk of canine zoonoses in human populations.Material and MethodsThe presence of parasites was examined in 450 faecal samples collected from eight zones of Zanjan province, northwest Iran from June to N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 39 publications
1
17
1
2
Order By: Relevance
“…10,41 A more recent study reported a prevalence of 19.1% in stool samples collected in urban streets and farms in Iran. 42 In regard to developed countries, Mateus found 59.8% of excrements collected from public areas in Portugal testing positive to gastrointestinal parasites, whereas in Slovakia, a parasitic contamination of 29.9-46.8% was detected. 9,43,44 In Turkey, 32.1% of cat and 28.4% of dog stool samples collected in an urban setting were found to be contaminated.…”
Section: Discussionmentioning
confidence: 98%
“…10,41 A more recent study reported a prevalence of 19.1% in stool samples collected in urban streets and farms in Iran. 42 In regard to developed countries, Mateus found 59.8% of excrements collected from public areas in Portugal testing positive to gastrointestinal parasites, whereas in Slovakia, a parasitic contamination of 29.9-46.8% was detected. 9,43,44 In Turkey, 32.1% of cat and 28.4% of dog stool samples collected in an urban setting were found to be contaminated.…”
Section: Discussionmentioning
confidence: 98%
“…Parasitic infections, particularly those capable of zoonosis, are the most important health, economic, and social problems in developing countries, including Iran. Carnivores are definitive or reservoirs hosts for more than 60 zoonotic parasites [ 1 , 2 ]. The presence of these animals in close contact with people constitutes a high potential risk of infection, especially for children due to their poor hygiene relative to adults and higher exposure to contact with contaminated soil containing parasite eggs or cysts.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have been performed to compare the prevalence of Giardia lamblia infection by age, sex, and diarrhea in infected dogs, cats, rabbits, sheep, goats, and cattle. [33][34][35][36][37] A significant difference between infection rates in various age groups or between gender was not observed in dogs. 33,34 While the prevalence of Giardia lamblia is appreciably higher in diarrheic cats, rabbits and cattle compared with non-diarrheic ones.…”
Section: Prevalence Of Giardia In Domestic Animalsmentioning
confidence: 99%
“…[33][34][35][36][37] A significant difference between infection rates in various age groups or between gender was not observed in dogs. 33,34 While the prevalence of Giardia lamblia is appreciably higher in diarrheic cats, rabbits and cattle compared with non-diarrheic ones. Also the infection is more prevalent in younger animals than older animals.…”
Section: Prevalence Of Giardia In Domestic Animalsmentioning
confidence: 99%